Database and expert systems applications : 30th International Conference, DEXA 2019, Linz, Austria, August 26-29, 2019, Proceedings.: 30th International Conference, DEXA 2019, Linz, Austria, August 26-29, 2019, Proceedings. Part II (2019) - Unknown
No abstract available